Effect of conditional deletion of cytoplasmic dynein heavy chain DYNC1H1 on postnatal photoreceptors - Dahl, Tiffanie M. (PLoS One, 2021)
Cytoplasmic dynein (dynein 1), a major retrograde motor of eukaryotic cells, is a 1.4 MDa protein complex consisting of a pair of heavy chains (DYNC1H1) and a set of heterodimeric noncatalytic accessory components termed intermediate, light intermediate and light chains. DYNC1H1 (4644 amino acids) is the dynein backbone encoded by a gene consisting of 77 exons. We generated a floxed Dync1h1 allele that excises exons 24 and 25 and truncates DYNC1H1 during Six3Cre-induced homologous recombination. Truncation results in loss of the motor and microtubule-binding domain. Dync1h1(F/F);Six3Cre photoreceptors degenerated rapidly within two postnatal weeks. In the postnatal day 6 (P6) Dync1h1(F/F);Six3Cre central retina, outer and inner nuclear layers were severely disorganized and lacked a recognizable outer plexiform layer (OPL). Although the gene was effectively silenced by P6, DYNC1H1 remnants persisted and aggregated together with rhodopsin, PDE6 and centrin-2-positive centrosomes in the outer nuclear layer. As photoreceptor degeneration is delayed in the Dync1h1(F/F);Six3Cre retina periphery, retinal lamination and outer segment elongation are in part preserved. DYNC1H1 strongly persisted in the inner plexiform layer (IPL) beyond P16 suggesting lack of clearance of the DYNC1H1 polypeptide. This persistence of DYNC1H1 allows horizontal, rod bipolar, amacrine and ganglion cells to survive past P12. The results show that cytoplasmic dynein is essential for retina lamination, nuclear positioning, vesicular trafficking of photoreceptor membrane proteins and inner/outer segment elaboration.